Discovery of a 2′-fluoro-2′-C-methyl C-nucleotide HCV polymerase inhibitor and a phosphoramidate prodrug with favorable properties. Issue 8 (15th April 2017) - Kirschberg, Thorsten A.; Metobo, Sammy; Clarke, Michael O.; Aktoudianakis, Vangelis; Babusis, Darius; Barauskas, Ona; Birkus, Gabriel; Butler, Thomas; Byun, Daniel; Chin, Gregory; Doerffler, Edward; Edwards, Thomas E.; et al.
Graphical abstract: Abstract: A series of 2′-fluorinated C -nucleosides were prepared and tested for anti-HCV activity. Among them, the triphosphate of 2′-fluoro-2′- C -methyl adenosine C -nucleoside (15 ) was a potent and selective inhibitor of the NS5B polymerase and maintained activity against the S282T resistance mutant. A number of phosphoramidate prodrugs were then prepared and evaluated leading to the identification of the 1-aminocyclobutane-1-carboxylic acid isopropyl ester variant (53 ) with favorable pharmacokinetic properties including efficient liver delivery in animals.